The First Decade with the Swedish Prescribed Drug Register – A Systematic Review of the Output in the Scientific Literature. Issue 5 (24th May 2016) - Wallerstedt, Susanna M.; Wettermark, Björn; Hoffmann, Mikael
Abstract: The aim of this study was to quantify and characterize the scientific output from the Swedish Prescribed Drug Register (SPDR) the first decade after its establishment. A systematic literature search was performed in Medline, EMBASE and PubMed (2005–2014). Additional publications were identified by personal knowledge, reference lists, contact with active authors and a citation search in Web of Sciences. Publications using SPDR data were included in the analysis and characterized regarding study type, presence of patient‐level record linkage, target population and topic. A total of 719 publications were identified in the literature search and an additional 148 by other strategies. Three hundred and thirty‐eight studies fulfilled the inclusion criteria. The majority were analytic (n = 166; 49.1%) or descriptive (n = 100; 29.5%). The remaining studies focused on validation (n = 20; 5.9%), health economics (n = 16; 4.7%) or miscellaneous (n = 36; 10.7%). The analytic studies investigating effects of drug exposure focused mainly on safety (n = 46) and/or effectiveness (n = 24). The first publications appeared in 2007 (n = 6), and in 2014, 90 articles using SPDR were published. Over the years, linkage with other registers using the personal identity number increased (0–88.9% of the publications). The population was often selected by age (49.7%), condition (45.0%) and/or drug (22.8%) and concerned predominantly psychiatric (29.0%) and cardiovascular (20.4%) diseases. In conclusion, this study illustrates that the establishment of a nationwide individual‐based register on dispensed prescription drugs facilitates an encouraging development of pharmacoepidemiological research, both regarding the number of publications and the scientific level of the analyses.